Sobre as ações do PIBID/matemática na constituição de saberes docentes de ex-bolsistas desse programa na Universidade Federal de Santa Maria - Reisdoerfer, Carmen (2015)
This study aimed to analyze, based on interviews with three ex-exhibitioners from Programa Institucional de Bolsa de Iniciação à Docência (PIBID), a Mathematics subproject of UFSM today Basic Education teachers and on official documents related to PIBID, the influences of the actions developed by this program in the constitution of teaching knowledge of these former students. In order to develop this qualitative research on the initial formation of Basic Education mathematics teachers we took as theoretical and methodological reference Maurice Tardif‟s studies with regard to teaching knowledge and, when it comes to oral history, the current parameters proposed by Grupo de História Oral e Educação Matemática (GHOEM), coordinated by professor Antonio Vicente Marafioti Garnica. The analysis of the narratives inspired by the work of Maria Edneia Martins-Salandim occurred in two stages: an analysis of the singularities and an analysis of the convergences. In the analysis of the singularities we sought to emphasize the scenario in which the story of each of the ex-exhibitioner has unfolded, as well as to highlight what most impressed us in each of the narratives. In the analysis of the convergences we made a discussion and brought out the present evidences from reports and narratives of the constitution of teaching knowledge from the participants on the influence of the actions developed in PIBID. Therefore, we listed three categories of analysis: professional knowledge; experiential knowledge; disciplinary and curricular knowledge. We emphasize that, according to the data, the actions carried out in PIBID have influenced the constitution of the four types of teaching knowledge, especially professional knowledge in what concerns the use of methodologies and varied resources, as well as experiential knowledge through the contact with Basic Education teachers and the development of classroom activities with Basic Education students. In addition, the participation in PIBID has also influenced participants‟ teaching practice mainly in the way they teach, by making use of features such as games and Information and Communication Technologies. The participation in PIBID has contributed to change the conception of what being a teacher means and it has had a decisive role in the initial formation of the ex-exhibitors since it has enabled their early insertion in schools, contributing to teaching learning and knowing the reality of the classroom.